A heterogeneous bifunctional carbon nanocatalyst from plastic waste to efficiently catalyze waste cooking oil into biodiesel - Hazmi, Balkis; Rashid, Umer; Kawi, Sibudjing; Wan Mokhtar, Wan Nur Aini; Ahmad Ahangar, Firdous; Choong, Thomas Shean Yaw; Tsubota, Toshiki; A. Alharthi, Fahad; Ngamcharussrivichai, Chawalit (Multidisciplinary Digital Publishing Institute, 2022)
In this study, black carbon derived from polyethylene terephthalate (PET) wastes was utilized as the precursor for heterogeneous bifunctional nanocatalyst, which successively catalyzed waste cooking oil into biodiesel. The nano-sized catalysts were prepared by impregnation method with different heat treatment techniques, such as reflux, hydrothermal, and microwave solvothermal, to provide good distribution of K2O and NiO particles on PET activated carbon mesoporous surface. The sample treated with microwave solvothermal technique (MAC-K2O-NiO) exhibited a high surface area of 120 m2/g with good dispersion of nanoparticles, as shown by FESEM image, large crystallite size of 62.2 nm, and consisted of a highest density of basicity (2.58 mmol/g) and acidity (1.79 mmol/g) for improving transesterification to a maximum yield. The catalytic transesterification of MAC-K2O-NiO was optimized with 3 wt.% of catalyst loading, 18: 1 methanol-oil molar ratio, 65 ◦C for 3 h of reaction, with a maximum yield of 97.2%. The catalyst reusability was performed, and it was found to maintain the catalytic activity up to six reaction cycles, with a yield of 72.9%. The physiochemical quality of the optimized biodiesel was examined in accordance with the American Society for Testing and Materials, ASTM D6751 testing method.